Sub-Regional Economic Cooperation in Southeast Asia: ITRO's Effect to Rubher's FDI lnflows & Indonesia's Rubber Economic Multipliers - Verico, Kiki; Batubara, Williater Leonardo (Institute for Economic and Social Research, 2010)
.